Declaração de (in)constitucionalidade no sistema jurídico brasileiro : a interpretação conforme a Constituição e a técnica de decisões manipulativas aditivas pelo Superior Tribunal Federal - Araújo, Roberto Alcântara de Oliveira (2018)
With social maturation and full democracy, society is now demanding from the State the realization of the fundamental rights established in the Constitution. The core of the work is found in the disrespect or non-fulfillment of fundamental commands and in the Judiciary work, which began to exercise a necessary normative activity, in the mission to rectify such determinations and omissions, promoting the interpretation and application of the Constitution. Which, at the same time that guarantees the primacy of constitutional commands, opens up opportunities for ambiguities, uncertainties and legal insecurity for citizens and for the Powers harmony. This paper aims to reach conclusions, pointing out that the democracy concept represents more than the simple majority rule and that the Judiciary seeks its legitimacy in the argumentative force, through a fair and participatory process, with the desiderato of the effectiveness of fundamental rights and promotion of the Democratic State of Law, through interpretation according to the Constitution tecniques with manipulative/modifying additive effectiveness, overcoming the classic concept of the “negative legislator”. Extending or restricting the meaning of the norm, many times the judicial decision presents itself as a modification of the original normative sense established by the legislative power, configuring a hypothesis of acting by the Judiciary as a "positive legislator." The creative act in interpretations according to the Constitution with manipulative/modifying effectiveness is a technique of saving the law or unconstitutional normative act, as well as technique of decision. The approach in these manipulative decision-making techniques of (in)constitutionality declaratory decisions poses the problematic of the limits and conditions of the performance of the country's judicial power, with emphasis on the Federal Supreme Court.